2017
DOI: 10.3847/1538-4357/834/1/68
|View full text |Cite
|
Sign up to set email alerts
|

Binary Black Holes in Dense Star Clusters: Exploring the Theoretical Uncertainties

Abstract: Recent N-body simulations predict that large numbers of stellar black holes (BHs) could at present remain bound to globular clusters (GCs), and merging BH-BH binaries are produced dynamically in significant numbers. We systematically vary "standard" assumptions made by numerical simulations related to, e.g., BH formation, stellar winds, binary properties of high-mass stars, and IMF within existing uncertainties, and study the effects on the evolution of the structural properties of GCs, and the BHs in GCs. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
148
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 100 publications
(172 reference statements)
6
148
1
Order By: Relevance
“…One of the interesting implications of their work is that the majority of BBHs would have mass ranges between 32 − 66 M⊙, and the contribution of cluster-origin BBHs would be roughly 14 per cent among the all merging BBHs in the local Universe. Adapting similar Monte-Carlo models, Chatterjee et al (2017) examined how different initial assumptions affect the cluster's evolution and properties of BH populations. They concluded that initial mass function, stellar wind, natal kicks are most important factors to affect the number of BBHs or properties of BH populations formed in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…One of the interesting implications of their work is that the majority of BBHs would have mass ranges between 32 − 66 M⊙, and the contribution of cluster-origin BBHs would be roughly 14 per cent among the all merging BBHs in the local Universe. Adapting similar Monte-Carlo models, Chatterjee et al (2017) examined how different initial assumptions affect the cluster's evolution and properties of BH populations. They concluded that initial mass function, stellar wind, natal kicks are most important factors to affect the number of BBHs or properties of BH populations formed in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in initial N and r v capture both of these effects. While the merger rates do depend on other variations, e.g., in the initial binary fraction and binary orbital properties of high-mass stars, the stellar IMF, and the distribution of natal kicks, the mass distribution of BBHs merging in the local universe is insensitive to these variations (Chatterjee et al 2017). Figure 2.…”
Section: Variation Due To Initial Cluster Propertiesmentioning
confidence: 99%
“…The process involved here is fundamentally different from BBH formation in isolation. A negligible fraction of BBHs formed in dense massive star clusters are primordial, and none with t delay 1 Gyr are composed of BHs formed from stars that were born in that binary (e.g., Chatterjee et al 2017). As massive stellar binaries evolve in dense star clusters, even if they were initially hard, mass loss from stellar winds and compact object formation can make these binaries soft.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations